Slugs control methods (Deroceras sp. Müller) in lettuce and broccoli crops - Astrid Santacruz (Agronomía Colombiana, 2011)
At the Botana experimental farm of Universidad de Nariño, the effect of different management practices of slugs was evaluated, using a randomized block design with five treatments (beer traps, milk traps, sisal bags, metaldehyde, and a control) and six repetitions. The evaluated variables were: captured individuals, affected plants and damage index that were estimated by analysis of variance and Tukey comparison tests. The results show highly significant differences between treatments in different phenological crops stages, the most effective were the metaldehyde and the beer trap with a caught individual number of 89 for lettuce and 126 for broccoli, being the treatments with lower percentages of affected plants. The damage index was evaluated based on percentages and proposed scales to observed crops damage, considering that the treatments described above stood out with mild damage index. This allows involved the beer treatment in an integrated management program for slugs as an alternative for reducing the pest population.